Driving Customer Loyalty through Customer Satisfaction in Online Shopping: The Role of Brand Image, Price, Trust and Website Quality - Rimsha Shafiq (The Lahore Journal of Business)
The relationship between brand image and loyalty in online shopping has gained significant attention in the marketing literature. Despite this attention, the specific path linking brand image to customer loyalty remains unclear. This study delves into the sequential and parallel mediations between brand image and customer loyalty, aiming to identify the effects of brand image, price, trust and website quality on customer loyalty through the mediation of customer satisfaction. Employing a parallel and sequential mediation model, this research addresses the practical implications for emerging e-commerce businesses. For data collection, an online questionnaire survey